2003
DOI: 10.1046/j.1464-410x.2003.04170.x
|View full text |Cite
|
Sign up to set email alerts
|

Desmopressin in elderly patients with nocturia: short‐term safety and effects on urine output, sleep and voiding patterns

Abstract: Desmopressin was well tolerated in elderly patients with nocturia, but the results suggest that serum sodium should be measured before and after a few days of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 17 publications
0
25
1
1
Order By: Relevance
“…The prevalence of hyponatremia found is similar to that described in a recent meta-analysis (Weatherall, 2004), which among other trials included the all male study in the present analysis. A previous trial in elderly indicated that the risk of desmopressin-induced hyponatremia increased with age, cardiac disease and increasing 24-hour urine volume (Rembratt et al, 2003). Patients with cardiac disease were excluded from the present trials, however, the findings on age and 24-hour urine volume were confirmed.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…The prevalence of hyponatremia found is similar to that described in a recent meta-analysis (Weatherall, 2004), which among other trials included the all male study in the present analysis. A previous trial in elderly indicated that the risk of desmopressin-induced hyponatremia increased with age, cardiac disease and increasing 24-hour urine volume (Rembratt et al, 2003). Patients with cardiac disease were excluded from the present trials, however, the findings on age and 24-hour urine volume were confirmed.…”
Section: Resultsmentioning
confidence: 68%
“…The incidence of hyponatremia reported in nocturia has been significantly higher, with 12-22% of patients experiencing one or more episodes of serum sodium concentration below normal range (Lose et al, 2003;Lose et al, 2004;Mattiasson et al, 2002;Rembratt et al, 2003). Serum sodium concentration has been assessed in many clinical trials involving desmopressin, but rarely as frequently as in the large nocturia trials published by Mattiasson et al and Lose et al Consequently, it is expected that these trials unearth a higher frequency of non-symptomatic low serum sodium concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Subjects with co-morbidity or medication use that could a¡ect serum sodium could have a di¡erent, and presumably higher, incidence of hyponatremia than the majority of subjects included in this analysis. Although it is reassuring that the Rembratt et al [2003] did include subjects who used diuretics and had other co-morbidity it is important to note that the follow up time for this study was only 3 days.…”
Section: Discussionmentioning
confidence: 99%
“…An important issue regarding whether this analysis can be generalised is that apart from one study [Rembratt et al, 2003] all of the studies included in the analysis excluded subjects who had cardiac or renal co-morbidity or used drugs, such as diuretics, that could a¡ect the serum sodium level. Subjects with co-morbidity or medication use that could a¡ect serum sodium could have a di¡erent, and presumably higher, incidence of hyponatremia than the majority of subjects included in this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…La hiponatremia puede originar diversos eventos adversos, desde cefalea leve, náuseas, vómitos y anorexia hasta pérdida de conciencia, convulsiones y la muerte. En un metaanálisis se ha comunicado que el riesgo de hiponatremia ronda el 7,6% 26 , y parece aumentar con la edad, las cardiopatías y un volumen alto de orina en 24 horas 27 .…”
Section: Desmopresinaunclassified